The Living Blue: Tracing the Footprints of the Blue Economy in Bantul's Coast - Fikhi Cahyani; Dini Yuniarti (IECON: International Economics and Business Conference, 2025)
Implementing the blue economy concept seeks to preserve environmental stability, thereby fostering sustainable development. Therefore, it's crucial to assess the understanding of local government, fishermen, and especially coastal communities regarding their support for successful blue economy implementation. This study aims to determine the understanding of blue economy among coastal communities in Bantul and to analyse its implementation within these communities. This research employs a descriptive approach, utilizing both quantitative and qualitative data. Primary data was collected through surveys using questionnaires and observations. The analysis was conducted using a descriptive qualitative approach. The findings indicate that all fishermen are not yet aware of the blue economy concept. Fishing practices still align with blue economy principles regarding fishing gear. The implementation of blue economy principles is evident in the treatment of unsold fish, where they are processed. Protected fish are returned to the sea to prevent extinction, aligning with blue economy principles. To further enhance blue economy implementation, the active participation of the government, fishermen, and local communities is essential. This can be achieved through socialization and education, especially for fishing communities, about the blue economy concept.